Avaliação da eficácia do Plano Nacional de Assistência Estudantil no sistema de restaurante universitário da Universidade Federal da Paraíba - Campus I: atores e fatores envolvidos na operacionalização - Mota, Cristiano de Sousa (2020)
With the objective of making possible the statistics of opportunities among all students and contributing to the improvement of academic performance, based on measures that seek to combat threats of repetition and dropout, the National Student Assistance Plan (PNAES) has become an important public policy implemented in Brazilian public higher education. In this sense, this research aimed to evaluate the National Student Assistance Plan (PNAES) in the university restaurant system of the Federal University of Paraíba (UFPB) of Campus I, with its actors and factors involved in the operationalization, in the period of 2017 to 2019. This research is marked by the theoretical framework on effectiveness, for example, Costa and Castanhar (2005) and Chauí (1999), or history of student assistance with Saviani (2010), and also on outsourcing with Kian (2006) and Silva (2011), among others. About the methodological procedures, this research was developed in a descriptive character with an exploratory qualitative approach. Data collection was carried out through documentary research, including order records, PRAPE reports and University Restaurants Superintendence, in addition to the Integrated System for Academic Activities Management (SIGAA) and the Institutional Development Plans (PDI) of UFPB. For an evaluation of the effectiveness of the funds of the National Student Assistance Plan (PNAES), no university restaurant system at the Federal University of Paraíba (UFPB) of Campus I, we consider an economic economy as categories of budget allocation and application of resources, considerations still a management dimension with cost / benefit categories, institutional dimension, company / UFPB ratio, cost savings and expansion of rights. A survey pointed out that no temporal return from 2017 to 2019, the results of the evaluation of the resources of the National Student Assistance Program (PNAES) showed that the program achieved its objectives regarding the categories of budget allocation, not referring to what was budgeted and allocated for UFPB and resource investment category, with no resource value allocated to the Dean of Student Assistance (PRAPE) and actually used in the university restaurant. However, it did not fully achieve the objectives in the demand / benefit categories, just because of the student's delay in using the aid by the student. In the institutional dimension category (PRAPE), the objectives were not fully achieved precisely because of the decrease in the number of meals served on Campus I. In the UFPB company relationship category, the objectives were not fully achieved due to the failure to adopt preventive measures in contracts and for end in the category of efficiency of spending it did not fully achieve the objectives due to the lack of a defined policy and mechanisms for monitoring evaluation.